TOMATO BIOCHEMICAL COMPOSITION AND QUALITY ATTRIBUTES IN DIFFERENT MATURITY FRUITS - Audrius Radzevičius; Pranas Viškelis; Jonas Viškelis; Rasa Karklelienė; Danguolė Juškevičienė; Pavelas Duchovskis (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
Maturity at harvest is very important attribute to tomatoes quality. This research showed that fully ripen tomato fruits had the highest amount of lycopene and β-carotene respectively 46.68 and 6.22 g kg-1. Therefore, it was determined correlation between amount of carotenoids and tomato ripening stages. Tomato fruit flesh lost it’s firmness through ripening period from 82.54 till 15.24 N cm-2. Fruit ripeness stage at harvest determines tomatoes biochemical composition and quality. Carotenoids (β-carotene, lycopene) syntheses during fruit ripening were the results of tomato colour and nutrition value changes, which results to correlation between colour indexes and tomato fruit quality attributes such as: hue angle (h°) and lycopene, colour index a* and lycopene, flesh firmness and hue angle (h°), skin firmness and chroma (C).